Comparative Repeat Profiling of Two Closely Related Conifers (Larix decidua and Larix kaempferi) Reveals High Genome Similarity With Only Few Fast-Evolving Satellite DNAs - Heitkam, Tony; Schulte, Luise; Weber, Beatrice; Liedtke, Susan; Breitenbach, Sarah; Kögler, Anja; Morgenstern, Kristin; Brückner, Marie; Tröber, Ute; Wolf, Heino; Krabel, Doris; Schmidt, Thomas (Frontiers in Genetics, 2021)
In eukaryotic genomes, cycles of repeat expansion and removal lead to large-scale genomic changes and propel organisms forward in evolution. However, in conifers, active repeat removal is thought to be limited, leading to expansions of their genomes, mostly exceeding 10 gigabasepairs. As a result, conifer genomes are largely littered with fragmented and decayed repeats. Here, we aim to investigate how the repeat landscapes of two related conifers have diverged, given the conifers’ accumulative genome evolution mode. For this, we applied low coverage sequencing and read clustering to the genomes of European and Japanese larch, Larix decidua (Lamb.) Carrière and Larix kaempferi (Mill.), that arose from a common ancestor, but are now geographically isolated. We found that both Larix species harbored largely similar repeat landscapes, especially regarding the transposable element content. To pin down possible genomic changes, we focused on the repeat class with the fastest sequence turnover: satellite DNAs (satDNAs). Using comparative bioinformatics, Southern, and fluorescent in situ hybridization, we reveal the satDNAs’ organizational patterns, their abundances, and chromosomal locations. Four out of the five identified satDNAs are widespread in the Larix genus, with two even present in the more distantly related Pseudotsuga and Abies genera. Unexpectedly, the EulaSat3 family was restricted to L. decidua and absent from L. kaempferi, indicating its evolutionarily young age. Taken together, our results exemplify how the accumulative genome evolution of conifers may limit the overall divergence of repeats after speciation, producing only few repeat-induced genomic novelties.